The Influence of Extraosseous Talar Vascular Luminal Diameter on the Development of Osteochondral Lesions of the Talar Dome - Lercan Aslan MD; Samir Ghandour MD; Cihad C. Gedik; Soheil Ashkani-Esfahani MD; Daniel Guss MD, MBA; Gregory R. Waryasz MD; Lorena Bejarano-Pineda MD; Christopher W. DiGiovanni MD; John Y. Kwon MD (Foot & Ankle Orthopaedics)
Category: Ankle; Trauma Introduction/Purpose: Osteochondral lesions of the talus (OLT) impact both sedentary individuals and athletes, affecting both daily function as well as athletic performance. Purported causations include trauma, genetics, and hypovascularity. Although it is known that the talar dome’s vascularity is mainly supplied the posterior tibialis artery (PTA) and to a lesser degree the sinus tarsi artery (STA), the pathophysiological impact of talar dome hypovascularity on OLT remains poorly studied. Our first hypothesis was that the patients with OLT have a lower diameter of PTA (dPTA) and STA (dSTA), and the second hypothesis was that among the group of the patients with OLT, the patients that require surgery have a lower d PTA and dSTA. Methods: This was a retrospective study that included 77 patients with OLT, and for the control group 77 patients with peroneal tendinitis. To mitigate the effect of comorbidities the patients between 30 to 40 years of age were included and the ones with a history of smoking, diabetes, rheumatologic, and peripheral artery diseases were excluded. The dPTA measurements were done in three different levels for all groups: at the level of 1 cm above plafond, at the level of plafond and at the level of medial malleolar tip (MMT). dSTA was measured at the level of talar neck. Area, volume, depth, and localization of OLT were recorded, as well. Results: The study group had significantly lower dPTA at three levels (1.05±0.22mm, 0.99±0.18mm, 0.98±0.31mm, proximal to distal) compared to the control group (1.25±0.23mm, 1.20±0.22mm, 1.14±0.18mm, proximal to distal) (P< 0.001). The dSTA was also lower in study group as compared to control group (0.5±0.11mm vs. 0.57±0.08mm, respectively P=0.001). ROC Curve analysis revealed the cutoff values for OLT occurrence after ankle injury as; 1.115 mm for the level of 1 cm above plafond, 1.075 mm for the level of plafond,1.055 mm for the level of MMT, 1.085 mm for mean dTPA and 0.5665mm for dSTA (Table-1). A significant negative correlation was observed between OLT size area (mean: 42.24±24.76 mm 2 ) and arterial diameters (P< 0.01, P< 0.01, and P=0.014 for three different levels of dPTA and P< 0.001 for dSTA). Conclusion: Smaller dPTA and dSTA appear to be associated with the occurrence of OLT, with the defect size inversely correlated to arterial diameters. The determined cutoff values for dPTA may help clinicians identify high risk patients to develop OLT after an acute ankle injury. Further elucidation of these vascular abnormalities, particularly dPTA, could hold significant prognostic potential and be used to predict disease progression as well as the likelihood of surgical success in OLT treatment.